#TITLE_ALTERNATIVE# - (NIM 13204086), LUKY
Flashover of insulators in transmission and distribution system may cause costly outages for power companies and their customers. Industrial and/or coastal pollution of external insulation is a major cause for such events at the normal power frequency voltage of the systems. This final project reports the experimental results on the leakage current characteristics of ceramics under various simulated environmental conditions. The samples used are blocks of ceramics with dimension of 150 x 30 x 10 mm3. The specimens were made from same materials for outdoor ceramic insulators. The samples were put in a test chamber with controlled humidity and air pressure. AC voltage with frequency of 50 Hz was applied. The data from experimental (leakage current characteristics with respect to humidity change, leakage current characteristics with respect to air pressure change, and critical flashover voltage) were processed with Fast Fourier Transform. Fast Fourier Transform (FFT) was employed to understand the frequency domain characteristics of the leakage current signal and Total Harmonic Distortion (THD). Brief analysis were then made from those data to obtain the true and reliable characteristics of ceramic if it was used as high voltage insulator material.